Estimation of the energy potential (heat and electricity) Of bovine manure in Nicaragua 2023 - Díaz Robleto, Marlon José (The Scientific Journal "El Higo", 2023)
According to the Food and Agriculture Organization of the United Nations (FAO), livestock farming is one of the main causes of degradation of soil and water resources, and it also generates more greenhouse gases (GHG) than the transportation sector, due among other causes. to the volumes of excreta generated. In Nicaragua, the livestock sector is one of the main contributors to the country’s economic development, being the main emitter of GHG caused by enteric fermentation (methane). The objective of this research was to present a survey based on internationally accepted theoretical foundations to make estimates of the enteric generation of methane due to the deposition of livestock manure. Likewise, national literature containing calculations used in case studies and projects was used. pilots executed, with this theoretical support the energy potential (heat and electricity) of the excreta of Nicaraguan cattle was estimated. The research approach was quantitative with a theoretical perspective of critical extension and modeling using the equations contained in the theory, guides and documents used as primary and secondary sources. As a result of this research, it was estimated that the energy potential of the country’s bovine manure is 57,393.89 MWh per day or 46.374263493 TCal/day, said potential was estimated from the calculation of more than 9 million cubic meters of biogas per day that generate the more than 186 thousand tons of manure that the country’s livestock herd generates daily.